Metaverse and movitations for customer usage: A salient study in the fashion industry - Le Xuan , Cu; Nguyen Phuong , Thao; Nguyen Thi Linh , Trang; Pham Thu , Trang; Nguyen Thi Thu , Thao (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study aims to analyze factors that influence users’ intentions to utilize Metaverse in the fashion industry. A research framework is postulated through an association between the Technology Acceptance Model (TAM) and the Push-Pull-Mooring model (PPM). Data were accumulated from 300 users who tend to utilize Metaverse in the fashion in Hanoi using convenience sampling method, and were examined using structural equation modelling (SEM), SPSS, and AMOS software. Results reveal that TAM antecedents (i.e., perceived usefulness and ease of use) and PPM antecedents (i.e., habit) foster use intention towards Metaverse. Furthermore, self-efficiency, perceived enjoyment, and perceived compatibility significantly affect perceived usefulness and ease of use. The paper draws several crucial academic and managerial implications for scholars and practitioners (i.e., businesses and technology developers) to augment customer experience and usage behavior towards Metaverse in the fashion industry.